2014
DOI: 10.1152/ajpheart.00600.2013
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol exposure alters early cardiac function in the looping heart: a mechanism for congenital heart defects?

Abstract: Alcohol-induced congenital heart defects are frequently among the most life threatening and require surgical correction in newborns. The etiology of these defects, collectively known as fetal alcohol syndrome, has been the focus of much study, particularly involving cellular and molecular mechanisms. Few studies have addressed the influential role of altered cardiac function in early embryogenesis because of a lack of tools with the capability to assay tiny beating hearts. To overcome this gap in our understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 64 publications
6
84
1
Order By: Relevance
“…We have found that at 13% EtOH the severe inhibition of the heart is observed. Some other studies have also reported the inhibition of heart at later development of chick embryo (Karunamuni, Gu et al 2014). This confirms the role of EtOH in inhibition of heart development.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We have found that at 13% EtOH the severe inhibition of the heart is observed. Some other studies have also reported the inhibition of heart at later development of chick embryo (Karunamuni, Gu et al 2014). This confirms the role of EtOH in inhibition of heart development.…”
Section: Discussionmentioning
confidence: 87%
“…CAM is formed on day 7 of incubation. EtOH has been reported to affect the process of angiogenesis in CAM assay using chick embryo as model organism ( ) and yolk sac blood vessels system of early staged chick embryos (Karunamuni, Gu et al 2014). In an elegant study, it was reported that moderate dose of EtOH has positive effects on development of embryo particularly on vasculature of embryo (Gu, Elam et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In children whose mothers drank alcohol there are functional difficulties that are difficult to diagnose and classify, and often sensory integration dysfunction. For these children SI therapy is necessary and effective [10][11][12][13][14][15][16][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. This work, because of the breadth of statistical analysis, only shows the effects of SI therapy on gross motor function.…”
Section: Discussionmentioning
confidence: 99%
“…Karunamuni et al on this issue purport that as high as 54% of live-born children with FAS present with cardiac anomalies e.g. valvuloseptal defects and pulmonary stenosis [26] that can lead to developmental challenges and on-going medical care.…”
Section: Congenital Heart Defects and Fetal Alcohol Spectrum Disordermentioning
confidence: 99%